Revealing The Economic Viability of Railway Investments (Case Study: Restoring Your Railway Programme, United Kingdom) - Alfian Nur, Zulhazmi; Muthohar, Imam (Journal of the Civil Engineering Forum, 2024)
The UK’s ”Restoring Your Railway” (RYR) programme aims to reopen abandoned railway infrastructure to foster local economic growth. However, since 2020, only 30% of RYR proposals have progressed, revealing challenges in the methodological approach, especially for projects introducing rail as a new mode. The current unimodal approach for estimating user benefits in such projects is considered inadequate. To address this, a Cost-Benefit Analysis (CBA) with improved methods for user benefit estimation has been conducted, compared with existing cases to determine if it results in a better Benefit-Cost Ratio (BCR). Historically, early appraisal methods relied on the Strategic Outline Business Case (SOBC), which took six months and incurred costs of approximately Rp. 1.5 billion. To expedite project delivery, sensitivity analysis explores circumstances under which RYR projects are socially justifiable across different Value for Money scenarios. Additionally, a comparative analysis is performed between the UK and Indonesian approaches. This study introduces a new CBA approach, focusing on user benefit estimation and conducting sensitivity analysis on key determinants. The mathematical CBA model, modified for the value of time and diversion factor, forms the basis for sensitivity analysis on BCR, travel time savings, capital and operational costs, diversion factor, and GDP growth. Testing the model against business cases reveals a 17-20% reduction in the required demand for the same BCR compared to conventional CBA approaches, suggesting the new method captures additional benefits related to mode shifts. Sensitivity analysis highlights circumstances under which railway projects are likely to deliver acceptable value for money, considering various BCR values. Total order indices show that operational costs contribute 40% to the model output, followed by capital costs and GDP growth rate at 29% and 25%, respectively. Surprisingly, the In-Vehicle Time (IVT) for trains has only a small contribution, ranging from 1.83% to 4%.